REPRESENTASI PERAN GENDER PADA IKLAN VIDEO TUKAR TEMPAT DI KANAL YOUTUBE CERDAS BERKARAKTER KEMENDIKBUD RI - Elizabeth Rose Marie Yudistanti; Catur Suratnoaji (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
Advertising is a form of mass media product that presents various benefits. In modern times, advertising has developed so that it is made in new media in the form of social media. This study discusses the Indonesian Ministry of Education and Culture's